Strong Desires and Strategies of Self-control: A Semiotic Approach to Food Cravings - Nielsen, Annemette; Micheelsen, Arun (Signs - International Journal of Semiotics, 2011)
A semiotic analysis of qualitative interviews with obese individuals shows experiences of ‘food cravings’ (i.e. strong, temporary, desires to eat that are generally directed on specific types of food) to be instances of semiosis that intersect biological, psychological and cultural spheres. In its analysis, the article introduces a new distinction between non-symbolic and symbolic dominance in food craving. It also describes ways in which food cravers use different semiotic strategies to achieve self-control by manipulating the semiosis of food craving. It is suggested that the semiotic framework offers an approach that could be fruitful both in future interdisciplinary studies and intervention programmes relating to food craving.